Interpersonal Trauma Among Women and Men Receiving Buprenorphine in Outpatient Treatment for Opioid Use Disorder - Martin, Caitlin E. (Violence against women, 2022)
People with opioid use disorder (OUD) are vulnerable to negative health outcomes related to substance use and psychosocial issues, such as interpersonal trauma (IPT). Participants receiving buprenorphine completed a cross-sectional survey (July–September 2019). OUD outcomes were prospectively abstracted over a 28-week timeframe. More than a third reported recent IPT (40% women, 36% men). Sexual violence was more common among women than men (p = .02). For women only, IPT was associated with substance use during follow-up (β = 20.72, 95% CI: 4.24, 37.21). It is important for public health strategies in the opioid crisis to address IPT using sex- and gender-informed approaches.